Improving Elementary Students’ Personal Letter Writing Skills through E-Scrapbook Learning Media - Shafa Nisa Al-Iman; Mubarok Somantri; Marwan Pulungan (Universitas Pendidikan Ganesha, 2026)
Writing personal letters remained a challenge for elementary students due to limited exposure to interactive learning media and the continued use of conventional instructional approaches. This study examined the effectiveness of E-Scrapbook learning media in improving the personal letter writing skills of fifth-grade students. A quasi-experimental design with a one-group pretest–posttest model was employed, involving 18 students who had no prior experience with the media to avoid knowledge bias. Data were collected through a written performance test that measured students’ ability to organize letter structure, develop coherent ideas, and apply accurate language conventions. The data were analyzed descriptively to identify changes in performance before and after the intervention. The findings showed a substantial improvement in writing achievement, with the average score increasing from 61.67 on the pretest to 93.61 on the posttest. The N-Gain value of 0.839 indicated a high level of effectiveness. Students demonstrated clearer organization of ideas, improved structural accuracy, and more precise use of language features after using the media. They also expressed positive responses, reporting that the digital features made learning more engaging and easier to understand. Overall, the study concluded that E-Scrapbook served as an effective instructional tool that enhanced students’ writing competence and supported more meaningful and engaging learning experiences in elementary language education.